The Inter-American System of Human Rights and the right of access to public information in the jurisprudence of the Inter-American Court of Human Rights - Janampa Almora, Juan José (2019)
This paper intends to inform the functioning of the Inter-American Human Rights System and its main institutions such as the Inter-American Court of Human Rights and the Inter-American Commission on Human Rights. In this sense, it will be evaluated how the Inter-American System has been working in relation to the right of access to public information as a fundamental tool for the control of citizenship against authority and as a institution for the strengthening of democracy.